(untitled) (Research, Society and Development, 2021)
Fibro-osseous lesions are a group of lesions characterized by the replacement of normal bone with fibrous animal tissue and mineralized tissue. Among these lesions is that the juvenile ossifying fibroma, a rare benign fibro-osseous tumor, comprising approximately 2% of oral tumors affecting children and adolescents. consistent with its histopathological features, it’s subdivided into psammomatoid juvenile ossifying fibroma and trabecular juvenile ossifying fibroma. The psammomatoid variant is male, with a mean age of twenty-two years, and predominantly within the maxilla. this sort of tumor is typically discovered during a routine radiographic examination, and its cortical expansion may result during a detectable facial enlargement. Its treatment and prognosis are uncertain. For smaller lesions local excision or careful curettage are often performed. For rapidly growing and/or aggressive lesions, in masse resection with conservative margins associated or not with the utilization of bone grafts and reconstruction plates could also be necessary. The aim of this report is to explain the condition of a 26-year-old patient referred to the Hospital Universitário do Oeste do Paraná with a diagnosis of psammomatoid juvenile ossifying fibroma within the mandible. After clinical examination and analysis of imaging exams, endodontic treatment of elements 34 to 42 was performed. The treatment consisted of curettage, enucleation of the lesion and apicectomy of the teeth involved, evolving uneventfully postoperatively. The patient has been under follow-up for 01 year and 07 months.